2022
DOI: 10.1371/journal.pone.0274898
|View full text |Cite
|
Sign up to set email alerts
|

Social media addiction and emotions during the disaster recovery period—The moderating role of post-COVID timing

Abstract: Background Social media addiction, a recently emerged term in medical science, has attracted the attention of researchers because of its significant physical and psychological effects on its users. The issue has attracted more attention during the COVID era because negative emotions (e.g., anxiety and fear) generated from the COVID pandemic may have increased social media addiction. Therefore, the present study investigates the role of negative emotions and social media addiction (SMA) on health problems durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…Customers' urgency to use smartphones becomes especially important for their reassurance and performing tasks in their everyday lives (Rodríguez‐Torrico et al, 2020; Ruiz Mafé & Sanz Blas, 2006). Because of the individuals' need to stay connected, and the necessity for security and comfort, addictive behaviours with smartphones have shown a substantial intensification in the recent past (Chopdar et al, 2022; Nur‐A Yazdani et al, 2022; Parent & Shapka, 2020). Consistent with the extant literature, we affirm that smartphone addiction does impact m‐shopping intentions and frequency, meaning that users who are dependent on their smartphones due to their previous interaction with the mobile service or retailer, would have a higher intention to involve in m‐shopping and would purchase more frequently via mobile channels (Kang & Kurtzberg, 2019; Konok et al, 2016).…”
Section: Development Of Hypotheses and Research Frameworkmentioning
confidence: 99%
“…Customers' urgency to use smartphones becomes especially important for their reassurance and performing tasks in their everyday lives (Rodríguez‐Torrico et al, 2020; Ruiz Mafé & Sanz Blas, 2006). Because of the individuals' need to stay connected, and the necessity for security and comfort, addictive behaviours with smartphones have shown a substantial intensification in the recent past (Chopdar et al, 2022; Nur‐A Yazdani et al, 2022; Parent & Shapka, 2020). Consistent with the extant literature, we affirm that smartphone addiction does impact m‐shopping intentions and frequency, meaning that users who are dependent on their smartphones due to their previous interaction with the mobile service or retailer, would have a higher intention to involve in m‐shopping and would purchase more frequently via mobile channels (Kang & Kurtzberg, 2019; Konok et al, 2016).…”
Section: Development Of Hypotheses and Research Frameworkmentioning
confidence: 99%
“…Social media addiction has various negative effects, including damaging mental health [ 5 ], poor life satisfaction [ 10 ], and chronic physical issues, such as neck pain or headaches [ 11 ]. Some studies that focused on company employees have demonstrated that social media addiction leads to a reduction in sleeping hours [ 12 ], increased distraction at workplace [ 12 ], and impaired productivity [ 8 ].…”
Section: Introductionmentioning
confidence: 99%